The Influence of Psychological Empowerment on Workforce Agility of Office Staff Housing Provision Study Province of West Sulawesi - Rezki Amaliah; Andi Mustika Amin; Tenri S.P. Dipoatmodjo; Agung Widhi Kurniawan; Muh. Ikhwan Maulana Haeruddin (PT. Maju Malaqbi Makkarana, 2023)
This study aims to find out how the effect of psychological empowerment on the workforce agility of the employees of the housing supply work unit in the province of West Sulawesi. This study uses a qualitative descriptive approach through data collection by interviews and documentation and analyzed by reducing data, presenting data, and drawing conclusions and verification. The results of this study illustrate that psychological empowerment has an influence on the workforce agility of the employees of the housing supply work unit in the province of West Sulawesi, but it is not significant because there is one indicator of psychological empowerment that is not fulfilled, namely self-determination. On this indicator employees are limited in determining their own way of working because they are bound by contracts and rules that apply in the workplace. The indicators of unfulfilled workforce agility are proactive indicators. While other indicators are met. Based on the results of the research above, it is known that psychological empowerment has an insignificant effect on workforce agility.